Various ways of continuous intraocular pressure monitoring in glaucoma patients: a narrative review - Ramakrishnan G; Jemaima Che Hamzah; Sharanjeet-Kaur S (Pusat Perubatan Universiti Kebangsaan Malaysia, 2019)
Glaucoma is a group of neurodegenerative disease linked with imbalance in the aqueous humor flow due to resistance in the aqueous drainage system. This increases the intraocular pressure (IOP), which causes damage to the optic nerve head and leads to irreversible blindness. As IOP is the only treatable risk factor for glaucoma, its 24 hours biorhythm need to be understood before managing it. Monitoring IOP is a critically important part in the management of glaucoma. Various approach and technology have been initiated and on-going for a frequent, round-the-clock IOP measurement to determine the IOP peaks and fluctuations. We review the current innovative approach and its importance as well as discussing the shortcomings of each method to obtain the 24 hour IOP profile.